2021
DOI: 10.3390/atmos12081021
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Proteome Response to Drought Stress and Antioxidant Potential in Tomato (Solanum lycopersicum L.)

Abstract: Advances in proteome research have opened the gateway to understanding numerous metabolic pathways and fundamental mechanisms involved in abiotic stress tolerance. In the present study, the antioxidant capacity of four tomato genotypes i.e., Kashi Amrit, Kashi Anupam, EC-317-6-1, and WIR-4360 was determined under drought stress to ascertain the scavenging potential for reactive oxygen species (ROS). A significant increase in the superoxide dismutase (SOD), Ascorbate peroxidase (APX), and catalase (CAT) activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…On the one hand, reports revealed that drought stress increases ROS levels by engulfing antioxidant enzyme activities, such as decreased activities of SOD and CAT in rice [ 62 ], CAT in brassica [ 63 ], and CAT and POD in maize [ 64 ]. On the other hand, drought stress also enhances the enzymatic antioxidant defense system to reduce oxidative stress, such as higher activities of SOD, POD, and CAT in wheat [ 65 ], SOD and CAT in tomato plants [ 66 ], and SOD, POD, and CAT in oats [ 67 ]. In this study, drought stress decreased SOD activity, whereas CAT activity was statistically similar to WW.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, reports revealed that drought stress increases ROS levels by engulfing antioxidant enzyme activities, such as decreased activities of SOD and CAT in rice [ 62 ], CAT in brassica [ 63 ], and CAT and POD in maize [ 64 ]. On the other hand, drought stress also enhances the enzymatic antioxidant defense system to reduce oxidative stress, such as higher activities of SOD, POD, and CAT in wheat [ 65 ], SOD and CAT in tomato plants [ 66 ], and SOD, POD, and CAT in oats [ 67 ]. In this study, drought stress decreased SOD activity, whereas CAT activity was statistically similar to WW.…”
Section: Discussionmentioning
confidence: 99%
“…the increase in hepatic MDA level may be attributed to the fact that AF is metabolized by the cellular cytochrome P450 enzyme system (20),this leads to lipid peroxidation and cellular injury and ( 21) also might be due to significant reduction in the activities of enzymatic antioxidants like Gpx in level which is also observed in present study.The SOD and GPx as the key enzymes of antioxidant system can scavenge free radicals generated from oxidant stress, reduce oxidative damage and maintain cell structure (22).Antioxidants may protect cells from the damage caused by free radicals. Antioxidant nutrients and enzyme defenses are fundamental protectors against all forms of stress (23).…”
Section: Antioxidant Statusmentioning
confidence: 99%
“…Global climate change gives rise to numerous environmental cues including biotic and abiotic stresses, which affect crop productivity (Raza et al., 2019; Farooq et al., 2022). Among them, drought stress (DS) is a destructive natural threat to food security, affecting a substantial fraction of the overall population, mainly those living in arid and semi‐arid areas (Figure 1) (Alamri et al., 2020; Cheng et al., 2021; Rai et al., 2021; Varshney et al., 2021a). Decreased precipitation and altered rainfall models trigger regular DS globally (Figure 1) (Cheng et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, advanced, more stable, and sustainable crop production is necessary to withstand DS (Varshney et al, 2021a). Severe DS hampers crop yield by affecting plant growth, physiology, biochemistry, and reproduction (Yang et al, 2019;Cui et al, 2020;Rai et al, 2021). Plant tolerance and sensitivity to DS relies on various aspects including the drought's impact, duration, and intensity and the plant's genetic potential and development stage (Varshney et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%